Between pandemonium and pandemethics: responses to Covid-19 from theology and religions - Erbele-Küster, Dorothea (Evangelische Verlagsanstalt, 2022)
Frontmatter -- Cover -- Titel -- Impressum -- Content -- Introduction -- Part I: Contextual Perspectives -- Liberation Theologies Revisited in Times of Pandemic. A Prologue -- Poverty through the Optic of the "Danger of a Single Story" -- How the Pandemic Will Change Minjung Theology -- Fighting Against a Double Pandemic. Anti-Asian Racism, Covid-19, and the Role of Asian American Churches -- "But it was God's own mighty plan." American Religion, Global Pandemics, and the Hidden History of Racial Pandemonium -- "You live and do me nothing" (Aby Warburg). Dance of Death, Vanitas, and Covid-19 Representations and the Mastery of the Indomitable -- Memoria Passionis Subversiva. The Moral Power of Remembrance in the Pandemic - Through a Swedish Lens -- From a Temporary Crisis to Life under Conditions of Vulnerability. Reflections on two years of Corona from the perspective of the Protestant Churches in Germany -- Covid, Climate, Coloniality. Theological (In)verses from Pasifika -- Part II: Interreligious Perspectives -- Hinduism's Encounter with Covid-19 -- Buddhist Resources for Dealing with Crises -- Small Virus - Huge Impact. How Covid-19 Changed Judaism -- In Search for Liberating Love and Knowledge in the Face of a Pandemic - Interfaith Engagements -- Taking Refuge in Sacred Texts in Times of Crisis. Lament and Apocalyptic Visions in Interreligious Perspective -- Backmatter -- Weitere Veröffentlichungen.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Internationaler Vergleich; Religionsgemeinschaft; Pandemie; COVID-19; Religion; Theologie